Creating A Sustainable Future: How Muslim MSMEs In Central Java Integrate Social And Environmental Responsibility - Dessy Noor Farida; Fajar Adhitya; Aulia Rahmawati (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Central Java play a strategic role in the regional economy, acting as key drivers of local economic growth. However, despite their essential contributions, MSMEs in Central Java continue to face several challenges, particularly in addressing environmental and social concerns. This study aims to examine in greater depth how MSME actors, particularly Muslim entrepreneurs, respond to environmental and social issues and the implications of these responses on business performance. Data collection was conducted using questionnaires, and the research applied descriptive analysis techniques to a sample of 107 Muslim entrepreneurs in Central Java. The findings indicate that Muslim entrepreneurs place significant importance on social and environmental responsibility, recognizing that the sustainability of their businesses is closely tied to their contributions to the surrounding environment. The results of the study indicate that Muslim entrepreneurs of MSMEs in Central Java consider environmental and social responsibility as important factors for business sustainability. This awareness is based on the belief that business sustainability depends on the reciprocity between the environment and nature. Social responsibility has also been shown to contribute to improving business performance, both through improving employee performance, increasing customer satisfaction, and establishing a positive reputation in the eyes of the community. Thus, a business orientation that pays attention to social and environmental aspects is not only ethical but also has strategic implications for the performance and sustainability of MSMEs.